The Brazilian Wage Curve: New Evidence from the National Household Survey - Badi H. Baltagi; Bartlomiej Rokicki; Kênia Barreiro de Souza (Institute for the Study of Labor (IZA), 2014)
This paper reconsiders the Brazilian wage curve using individual data from the National Household Survey at 27 Federative Units over the period 2002 - 2009. We find evidence in favor of the Brazilian wage curve with an unemployment elasticity of -0.08 when the lagged unemployment rate is used as an instrument for current unemployment rate. We also find that males in Brazil are significantly more responsive to local unemployment rates (-0.13) than their female counterparts. In fact, we find that the unemployment elasticity for women is statistically insignificant. Applying gender specific unemployment rates, the elasticity for men decreases to -0.09, while the elasticity for women remains statistically insignificant. This paper also finds that the estimates for Brazilian wage curve are completely different for the case of formal and informal workers.
Keywords: C26; J30; J60; 330; wage curve; fixed effects; regional labor markets; household surveys; informal workers